A survey of bacterial blight (Xanthomonas oryzae pv. oryzae) resistance in rice germplasm from eastern and northeastern India using molecular markers. (October 2018) - Banerjee, Amrita; Roy, Somnath; Bag, Manas Kumar; Bhagat, Someswar; Kar, Meera K.; Mandal, N.P.; Mukherjee, Arup K.; Maiti, Dipankar
Abstract: Bacterial blight (BB), caused by Xanthomonas oryzae pv. Oryzae ( Xoo ), is one of the most serious diseases of rice causing a significant yield loss mostly in Asia and parts of Africa and poses a threat to the breakdown of varietal resistance. Development of resistant varieties carrying major resistance ( R ) gene(s) has been the effective way for controlling BB. The type of R gene(s) to be deployed depends on the predominant Xoo pathotypes. Identification of the R genes present in rice germplasm is a vital exercise. In the present experiment, phenotyping for BB resistance was carried out in 210 rice germplasm comprised of released varieties and landraces from eastern and northeastern India. Based on disease scoring, 95 released varieties being categorized into 29 resistant, 42 moderately resistant and 24 susceptible, while, 115 rice landraces were grouped into eight resistant, 38 moderately resistant and 69 susceptible accessions. Molecular screening for the presence and frequency of 10 BB resistance genes was made from a sub set of 70 genotypes, comprising 35 resistant, 21 moderately resistant and 14 susceptible entries. The frequency of R genes varied from 0 to 5 per genotype. The most frequent gene was Xa1 followed by Xa7  >  Xa4  >  Xa10  >  Xa11. A few entries such as Nua Kalajeera, Kalinga III, Naveen, CR Dhan 701, Swarna Sub1, Kalajeera, and ARC5791 possessed 3–5 genes. The findings indicated that Xa1, Xa7, and Xa11 had been frequently selected in breeding programmes, and the frequency of xa5, Xa8, xa13 and Xa21 should be increased in the released varieties in different combinations to achieve durable resistance. The resistant cultivars identified in the present study can be used directly as resistance donors in rice breeding as well as for identification of race-specific/broad spectrum sources of resistance against BB. Highlights: Assessment of bacterial blight resistance in 210 rice germplasm from eastern and northeaster India. The frequency of resistant and moderately resistant entries was higher in released varieties than in landraces. The number of BB R genes in a genotype varied from 0–5. The gene frequency is as follows: Xa1  > Xa7 > Xa4 > Xa10 > Xa11. Nua Kalajeera, KalingaIII, Naveen, CRDhan701, Swarna Sub1, Kalajeera, TapaswiniMAS, IR64MAS and ARC5791 recorded 3-5 R genes. Xa7, xa8 and Xa11 should be considered along with xa5 + xa13 + Xa21 for gene deployment in Eastern parts of India.